1989
DOI: 10.1093/ptj/69.8.671
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Effects of Transcutaneous Electrical Nerve Stimulation of Auricular, Somatic, and the Combination of Auricular and Somatic Acupuncture Points on Experimental Pain Threshold

Abstract: This study compared the effects of high intensity, low frequency transcutaneous electrical nerve stimulation of auricular, somatic, and combined auricular and somatic acupuncture points on experimental pain threshold measured at the wrist. Sixty-seven healthy adults, aged 18 to 39 years, were assigned randomly to one of four groups: 1) the Auricular Group (n = 17) received TENS to auricular acupuncture points, 2) the Somatic Group (n = 17) received TENS to somatic acupuncture points, 3) the Combined Group (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…26,49 Overall, TENS showed conflicting evidence of efficacy. Twenty-four trials reported positive outcomes 28,33,[36][37][38][39][41][42][43]45,[47][48][49][50]52,53,[55][56][57][58]61,64,65 (ie, a significant difference favoring TENS compared with an inactive control) and 19 trials reported negative outcomes 26,27,[29][30][31][32]34,35,40,44,46,51,54,59,60,62,63,66 (ie, no difference between TENS and an inactive control). No trials reported a significant difference favoring the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…26,49 Overall, TENS showed conflicting evidence of efficacy. Twenty-four trials reported positive outcomes 28,33,[36][37][38][39][41][42][43]45,[47][48][49][50]52,53,[55][56][57][58]61,64,65 (ie, a significant difference favoring TENS compared with an inactive control) and 19 trials reported negative outcomes 26,27,[29][30][31][32]34,35,40,44,46,51,54,59,60,62,63,66 (ie, no difference between TENS and an inactive control). No trials reported a significant difference favoring the control group.…”
Section: Resultsmentioning
confidence: 99%
“…Similar proportions of positive and negative trials recorded the outcome measurement with TENS switched on, [26][27][28][29][30][31][32][33]36,41,45,[49][50][51][52][54][55][56][57][58]63,68 switched off, 34,35,[37][38][39][40][42][43][44][46][47][48] or poststimulation. 53,[59][60][61][62]64,65 Specifically, with TENS switched on, 13 of 24 trials (54%) 28,33,36,41,45,49,50,52,[55][56]…”
Section: Timing Of Outcome Measurementmentioning
confidence: 99%
“…Noling et al (1988) found that a low frequency (1 Hz) with a high intensity (1000 μ A) elevated the pain threshold, and this effect peaked 5 to 10 min after stimulation and lasted from several hours to a few days [ 47 ]. Lein et al (1989) used TENS and also had the same result as above [ 48 ]. Sator-Katzenschlager et al (2003) found that auricular electrical stimulation is better than auricular manual acupuncture when decreasing pain [ 49 ].…”
Section: Clinical Applicationmentioning
confidence: 90%
“…Recent studies indicate that stimulating acupuncture points as a treatment for pain may be even more effective than TENS on other somatic points. 10,18,19 With respect to this study, the gate control theory best represents the affect of TENS on patients with burn pruritus. The exogenous stimulus provided by TENS appeared to override the patients' perception of pruritus.…”
Section: Discussionmentioning
confidence: 99%